Mechanism-Dependent Selectivity: Fluorocyclization of Unsaturated Carboxylic Acids or Alcohols by Hypervalent Iodine - Su, Jiaqi; Shu, Siwei; Li, Yinwu; Chen, Yong; Dong, Jinxiang; Liu, Yan; Fang, Yanxiong; Ke, Zhuofeng (Frontiers in Chemistry, 2022)
To understand the unprecedented difference between 6-endo and 5-exo selectivity in hypervalent Iodine(III) promoted fluorocyclization of unsaturated carboxylic acids or alcohols by difluoroiodotoluene, density functional theory (DFT) studies have been performed to systematically compare both the previous proposed “fluorination first and cyclization later” mechanism, and the alternative “cyclization first and fluorination later” mechanism. Our results revealed that the selectivity is mechanism-dependent. The unsaturated alcohol prefers the fluorination first and the 6-endo-tet cyclization later pathway, leading to the experimentally observed 6-endo ether product. In contrast, the unsaturated carboxylic acid plausibly undergoes the 5-exo-trig cyclization first, and the fluorination later to the experimentally observed 5-exo lactone product. The pKa property of the functional group of the substrate is found to play a key role in determining the reaction mechanism. The provided insights of the mechanism-dependent selectivity should help advance the development of fluorocyclization reactions with hypervalent iodine reagents.